GROWING AND GETTING GOOD GRADES? INTERPLAY PERSONAL GROWTH INITIATIVE, EXTRINSIC MOTIVATION, AND ACADEMIC PROCRASTINATION - Ika Raharja Salim; Livia Yuliawati (Psibernetika, 2021)
The inability of students to plan is one of the causes of academic procrastination behavior. The ability to plan can emerge from within the individual, which is described in the personal growth initiative or PGI. This study was conducted to see whether there is an influence from the individual's internal as seen from the personal growth initiative on academic procrastination behavior. Academic motivation is also an interesting variable to mediate the effect of personal growth initiative on academic procrastination, especially in this study out of three types of academic motivation, external was the chosen one. So that this study is able to show the influence on the behavior of academic procrastination in terms of the inner self which is mediated by the individual outside. The study was conducted by taking samples from six universities in Surabaya, public and state universities (N = 207). Data was taken using online and offline questionnaires. The results showed that PGI did not affect academic procrastination (βc' = - 0.004) either directly or through the mediation of extrinsic academic motivation (βb = - 0.002), but the results of data analysis showed that there was an effect of PGI on extrinsic academic motivation (βa = 0.459).